Nonviolent communication : a language of life [book club bag] + workbook - Rosenberg, Marshall B. (PuddleDancer Press, 2015)
"Most of us have been educated from birth to compete, judge, demand, and diagnose--to think and communicate in terms of what is 'right' and 'wrong' with people. At best, communicating and thinking this way can create misunderstanding and frustration. At its worst, it can lead to anger, depression, and even emotional or physical violence. [This book] uses stories, role-plays, and real-world examples to introduce the Nonviolent Communication (NVC) process. Far more than simple techniques, you'll learn to transform the thinking, language, and moralistic judgments that prevent the quality of relationships you've always wanted. Start to more easily resolve conflicts, get what you want without demands, hear the needs of others, strengthen your personal and professional relationships, and live your fullest potential. With Nonviolent Communication, you'll learn to: significantly improve your relationships with family, friends, and co-workers; stay peaceful in the face of judgment, criticism, and anger; speak, think, and listen in ways that inspire compassion and understanding; break patterns of thinking that lead to stress, depression, guilt, and shame; discover common ground with anyone, anytime, anywhere."--Book cover.